Kualitas Pelayanan Lembaga PAUD dan Dampaknya pada Kepuasan Orang Tua - Asti Amanda (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Early childhood is a period of rapid growth and development in a child's life. At this stage, children begin to form the foundations of their intelligence, character, and social and emotional abilities that will influence their future lives. Therefore, early childhood education plays a very important role in providing stimulation and learning experiences that are appropriate for their stage of development. In West Sumatra Province, public awareness of the importance of early childhood education services continues to increase along with the growing number of early childhood education institutions. However, the increase in the number of institutions has not been accompanied by an improvement in service quality. Many institutions still face obstacles such as a shortage of qualified teachers, a lack of facilities and infrastructure, and low teacher welfare. This situation has an impact on the quality of services received by children and the satisfaction of parents as service recipients. The results of this study are expected to provide a deeper understanding of the importance of improving service quality as an effort to create high-quality, competitive PAUD institutions that are able to meet the expectations of the community.